2006
DOI: 10.1192/bjp.bp.105.018150
|View full text |Cite
|
Sign up to set email alerts
|

Attention to the eyes and fear-recognition deficits in child psychopathy

Abstract: The ability to recognise fear is impaired in people with damage to the amygdala and, interestingly, in adult psychopathy. Here we confirm that deficits in recognising fear exist in children with psychopathic traits. We show for the first time that, as with patients with amygdala damage, this deficit can be temporarily corrected by simply asking them to focus on the eyes of other people. These data support models of psychopathy that emphasise specific dysfunction of the amygdala and suggest an innovative approa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

35
364
7
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 388 publications
(420 citation statements)
references
References 12 publications
35
364
7
5
Order By: Relevance
“…Youths who were high callous-unemotional traits had fewer correct responses to afraid faces, even controlling for violence and antisocial behavior. The deficits in afraid faces for youths high on callous-unemotional traits found are consistent with the findings reported by 13 who also found a significantly negative partial correlation. Using the corrected accuracy, a general deficit in labeling faces was found and no specific deficit for fear.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Youths who were high callous-unemotional traits had fewer correct responses to afraid faces, even controlling for violence and antisocial behavior. The deficits in afraid faces for youths high on callous-unemotional traits found are consistent with the findings reported by 13 who also found a significantly negative partial correlation. Using the corrected accuracy, a general deficit in labeling faces was found and no specific deficit for fear.…”
Section: Discussionsupporting
confidence: 82%
“…However, a general deficit in facial emotion recognition is not inconsistent with prior research. 18 Findings by 13 support poorer accuracy for faces in youths with high callous-unemotional traits, although not all negative coefficients Callous-Unemotional Traits 10 were significant. Most studies have neglected to adjust accuracy, and the results of the present study highlight the need to adjust for biases.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…In line with this idea we would then expect that catastrophizing about own or other's pain would lead to hypervigilance, and a higher detection of pain in others 40,69 whereas psychopathy would lead to a lower detection of and hyposensitivity for pain in others 18,55 .…”
Section: Introductionmentioning
confidence: 90%
“…Supporting this idea, the amygdala, a key structure implied in fear responses, plays a critical role in the evocation of the fearpotentiated startle reflex 21,39,46,60,61 . Furthermore, research on personal pain experience has consistently shown that participants display a fear-potentiated startle when experiencing or 18 anticipating pain 25,38,41,47 , particularly when pain is perceived as highly threatening 7 Observers' distress towards pain signals in others likely serve a protective function of preparing observers for dealing with impending threat 40 . Specifically, observers' distress responses may instigate avoid/escape tendencies 72,81 .…”
Section: Self-report Datamentioning
confidence: 99%